Double Stigma: the needs and experiences of lesbian, gay and bisexual people with mental health issues living in Wales - Tracey Maegusuku-Hewett (Stonewall Cymru, 2009)
Stonewall Cymru in partnership with Hafal, Mind Cymru and Journeys identified a need for an exploratory Wales- specific study to explore the needs and experiences of lesbian, gay and bisexual people who have experienced or have mental health issues. Funding was obtained from the Equalities and Human Rights Commission and researchers from Swansea University were commissioned to enable this preliminary piece of work. Stonewall Cymru and its partner mental health organisations anticipate this exploratory study will help shape policy and best practice. More specifically the objectives of the study were:· To research the experiences and needs of LGB people with mental health issues living in Wales;· To identify the key issues, concerns and aspirations of LGB people with mental health issues;· Based on the findings, to provide recommendations to policy makers, organisations and practitioners around inclusion and good practice with LGB people with mental health issues.